Analysis of Sustainable Food House Area Program and The Relationship with Food Security and Household Welfare (Case Study in Surakarta City) - Kurniawan, Yusrizal Yoga; Daerobi, Akhmad; Sarosa, Bambang; Pratama, Yogi Pasca (Jurnal Ilmu Ekonomi Terapan, 2018)
Kawasan Rumah Pangan Lestari is a program to optimize the utilization of environmental-friendly yards, and designed to help the fulfillment family quality and nutrition needs, foods diversification based on local resource, crops preservation, and family income improvement through household-based non-rice local food processing creative industry. This research aims to quantify the effectiveness of Kawasan Rumah Pangan Lestari program in Surakarta, and describe the correlation of program effectiveness toward the prosperity and food security of program implementer.This research employed a descriptive quantitative methode. The research variable consists of the effectiveness, household prosperity, and household food security. Data collection methode used a questionnaire and interview that compiled from 40 respondents of 10 KRPL group. This research used a purposive sampling technique. Data analysis technique which to measure the program effectiveness evaluated to sample test statistic, and to describe the correlation of program effectiveness toward the prosperity and food security of program implementer used a Spearman test correlation.The result of this research shows that implementation of the Kawasan Rumah Pangan Lestari program in Surakarta is effective, and there is a positive correlation between the program effectiveness toward the prosperity and food security of program implementer in Surakarta. The effectiveness of the Kawasan Rumah Pangan Lestari program in Surakarta could be improved by maximizing the quality of socialization among the members and counseling about utilization of planting media as the alternative to replace the limited fields. And the last is improved the quality and quantity of the monitoring from the related agencies intensely and regularly.